Tissue Factor – A Receptor Involved in the Control of Cellular Properties, Including Angiogenesis - Chen, Jiang; Bierhaus, Angelika; Schiekofer, Stephan; Andrassy, Martin; Chen, Baosheng; Stern, David M.; Nawroth, Peter P. (Thrombosis and Haemostasis, 2001)
Tissue factor (TF), the major initiator of blood coagulation, serves as a regulator of angiogenesis, tumor growth and metastasis. In several models, TF expression mediates upregulation of the proangiogenic vasular endothelial growth factor (VEGF) that can directly act on endothelial cells to promote vessel formation. This occurs through ligand binding, activation of signaling cascades, signal transduction and alteration of growth factor expression and is mediated by both, coagulation-dependent and -independent pathways. Depending on the cell type and the biological settings, TF seems to affect cellular properties through (i) factor VIIa (FVIIa)-dependent proteolysis of factor Xa (FXa) and thrombin and subsequent activation of proteinase activated receptor (PAR) -1 and PAR-2, (ii) through direct FVIIa signaling and mitogen activated protein (MAP) kinase activation, that is conferred by a not yet identified receptor, (iii) through interaction of FVII(a) proteolytic activity and signaling of the cytoplasmic domain and (iv) through cytoplasmic signaling independent of ligand binding. The role of phosphorylation of the cytoplasmic domain and the pathways controlling phosphorylation of TF remain poorly understood.
Keywords: Angiogenesis; vasculogenesis; VEGF; metastasis; tumor growth